Optineurin-mediated mitophagy as a potential therapeutic target for intervertebral disc degeneration - Hu, Zhilei; Wang, Yu; Gao, Xiaoxin; Zhang, Yuyao; Liu, Chenhao; Zhai, Yu; Chang, Xian; Li, Haiyin; Li, Yueyang; Lou, Jinhui; Li, Changqing (Frontiers in Pharmacology, 2022)
Low back pain is thought to be mainly caused by intervertebral disc degeneration (IVDD), and there is a lack of effective treatments. Cellular senescence and matrix degradation are important factors that cause disc degeneration. Mitochondrial dysfunction induced by oxidative stress is an important mechanism of cellular senescence and matrix degradation in the nucleus pulposus (NP), and mitophagy can effectively remove damaged mitochondria, restore mitochondrial homeostasis, and mitigate the damage caused by oxidative stress. Optineurin (OPTN) is a selective mitophagy receptor, and its role in intervertebral disc degeneration remains unclear. Here, we aimed to explore the effect of OPTN on H2O2-induced nucleus pulposus cell (NPCs) senescence and matrix degradation in a rat model of disc degeneration. Western blot analysis showed that OPTN expression was reduced in degenerative human and rat nucleus pulposus tissues and increased in H2O2-induced senescent NPCs. OPTN overexpression significantly inhibited H2O2-induced senescence and increased matrix-associated protein expression in NPCs, but OPTN knockdown showed the opposite effect. As previous reports have suggested that mitophagy significantly reduces mitochondrial damage and reactive oxygen species (ROS) caused by oxidative stress, and we used the mitophagy agonist CCCP, the mitophagy inhibitor cyclosporin A (CsA), and the mitochondrial ROS (mtROS) scavenger mitoTEMPO and confirmed that OPTN attenuated NPCs senescence and matrix degeneration caused by oxidative stress by promoting mitophagy to scavenge damaged mitochondria and excess reactive oxygen species, thereby slowing the progression of IVDD. In conclusion, our research suggests that OPTN is involved in IVDD and exerts beneficial effects against IVDD.